2006
DOI: 10.1002/ajpa.20517
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic approaches for understanding patterns of intracemetery biological variation

Abstract: This paper reviews studies of phenotypic inheritance and microevolutionary processes in archaeological populations using data on cranial and dental phenotypic variation, often referred to as paleogenetics or biodistance analysis. The estimation of biological distances between populations, or among individuals within populations, is one component of bioarchaeological research on past populations. In this overview, five approaches that focus on morphological variation within cemeteries are summarized: kinship an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
149
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 219 publications
(352 reference statements)
2
149
0
2
Order By: Relevance
“…Larsen, 1997;Pietrusewsky, 2000;Stojanowski and Schillaci, 2006) because of the moderate to high degree of heritability (Kieser, 1990;Scott, 1991;Dempsey and Townsend, 2001), absence of remodeling after crown completion, and generally better preservation of the crown (Hillson, 1996;Scott and Turner, 1997). All of the dental measurements used in this study were collected by one of the authors (W.M.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Larsen, 1997;Pietrusewsky, 2000;Stojanowski and Schillaci, 2006) because of the moderate to high degree of heritability (Kieser, 1990;Scott, 1991;Dempsey and Townsend, 2001), absence of remodeling after crown completion, and generally better preservation of the crown (Hillson, 1996;Scott and Turner, 1997). All of the dental measurements used in this study were collected by one of the authors (W.M.…”
Section: Methodsmentioning
confidence: 99%
“…Interpopulation phenotypic variation is formed through genetic drift (human settlement, population growth/decline) and gene flow (human migration) (Lane and Sublett, 1972;Spence, 1974;Konigsberg and Buikstra, 1995;Stojanowski and Schillaci, 2006). Matsumura's (2000) dental metric study on skeletal remains from four sites in the Atsumi Peninsula area (the Yoshigo, Inariyama, Ikawazu and Hobi shell mounds) revealed that most of the individuals from these four sites did not form clear sitespecific clusters, although some individuals from a given site formed tight clusters, which might have reflected close kinship.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its inception, the Relethford-Blangero model has been used in many biological anthropological investigations to examine changes in levels of gene flow as a means of exploring genetic relationships among and between populations (cf. Relethford et al 1997;Steadman 1998Steadman , 2001Powell and Neves 1999;Schillaci and Stojanowski 2005;Stojanowski and Schillaci 2006;Scherer 2007). …”
Section: Population Genetic Analysismentioning
confidence: 99%